Low fluoroscopy permanent His bundle pacing using a new electroanatomic mapping system (KODEX EPD). A multicenter experience. Issue 1 (30th December 2022) - Scarà, Antonio; Golia, Paolo; Grieco, Domenico; Borrelli, Alessio; De Ruvo, Ermenegildo; Bressi, Edoardo; Politano, Alessandro; De Luca, Lucia; Bruni, Giuseppe; Fagagnini, Alessandro; Panuccio, Marco; Rebecchi, Marco; et al.
Abstract: Background: His bundle pacing (HBP) may be a challenging procedure, often involving a long fluoroscopic time (FT) and a long procedural time (PT). We sought to evaluate whether the use of a new nonfluroscopic mapping (NFM) system, the KODEX‐EPD, is able to reduce FT and PT when mapping is performed by the pacing catheter rather than an electrophysiological mapping catheter. Methods and Results: We included 46 consecutive patients (77 ± 8 years; 63% male) who underwent HBP; in 22 a NFM‐guided procedure with the KODEX‐EPD system was performed (group 1), whereas in 24 a conventional fluoroscopy‐guided approach was used (group 2). Pacing indications were sick sinus syndrome in 13, atrioventricular block in 21, and cardiac resynchronization therapy in 12 cases. Both a lumen‐less fixed helix lead and a stylet‐driven extendable helix lead were used, respectively, in 24% and 76% of patients. HBP was successful in 22 patients (100%) in group 1 and 23 patients (96%) in group 2. The FT was significantly reduced in group 1 (183 ± 117 s vs 464.1 ± 352 s in group 2, p = .012). There were no significant differences between groups in PT and other procedural outcomes. Conclusions: The KODEX‐EPD system may be safely used in HBP procedures. It is effective in reducing ionizing radiation exposure, as evidenced by the significant drop in FT, without increasing PT. Abstract : His bundle pacing (HBP) may be a challenging procedure, often involving a long fluoroscopic time (FT) and a long procedural time (PT). The KODEX‐EPD system may be safely used in HBP procedures. It is effective in reducing ionizing radiation exposure, as evidenced by the significant drop in FT, without increasing PT.